Headhunting: simulation in the course human resources management in pandemic - Rodríguez Chokewanca, Ingrid Rossana; Ticona Condori, Madeleine Nanny; Pasaca Apaza, Diana Marleny (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The university adapted professional training to virtuality, thus adapting the theory and practice of the different subjects, in this new context the objective of this study was to develop a simulation game for the selection of human talent and describe the gaming experience in pandemic. With a quantitative methodological approach, non-experimental cross-sectional descriptive design, applied to students of the VIII cycle of the Human Resources Management course. It is concluded that the simulated game is a tool that facilitates learning in a virtual way, it also contributes to the learning of the proposed topic, in an organized, dynamic and fun way.